Thermosensitive Polymer-Modified Mesoporous Silica for pH and Temperature-Responsive Drug Delivery - Kokila Thirupathi; Madhappan Santhamoorthy; Sivaprakasam Radhakrishnan; Selvakumari Ulagesan; Taek-Jeong Nam; Thi Tuong Vy Phan; Seong-Cheol Kim (MDPI AG, 2023)
A mesoporous silica-based drug delivery system (MS@PNIPAm-PAAm NPs) was synthesized by conjugating the PNIPAm-PAAm copolymer onto the mesoporous silica (MS) surface as a gatekeeper that responds to temperature and pH changes. The drug delivery studies are carried out in vitro at different pH (7.4, 6.5, and 5.0) and temperatures (such as 25 °C and 42 °C, respectively). The surface conjugated copolymer (PNIPAm-PAAm) acts as a gatekeeper below the lower critical solution temperature (LCST) (<32 °C) and as a collapsed globule structure above LCST (>32 °C), resulting in controlled drug delivery from the MS@PNIPAm-PAAm system. Furthermore, the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay and cellular internalization results support the prepared MS@PNIPAm-PAAm NPs being biocompatible and readily taken up by MDA-MB-231 cells. The prepared MS@PNIPAm-PAAm NPs, with their pH-responsive drug release behavior and good biocompatibility, could be used as a drug delivery vehicle where sustained drug release at higher temperatures is required.